In-House Programming Is Not Passé: I Automating Originality. - Olsen, Kai A. (Computer (00189162), 2009)
The article discusses the advantages to firms of developing their own information technology (IT). Although commercial software packages are available for a variety of business applications, such "off-the-shelf" solutions are seldom optimal for companies with distinctive IT requirements. The author illustrates his point by examining the IT needs of a foundry that manufactures ship propeller blades. Proprietary software developed by the firm's IT staff enables it to fulfill customized orders and obtain strategic advantages.